The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/clep.s300394
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hysterectomy Incidence Rates During 2000–2015 in Denmark: Shifting from Abdominal to Minimally Invasive Surgical Procedures

Abstract: Background Hysterectomy (removal of the uterus) is a common surgical procedure in gynecology. Although minimally invasive surgical procedures have been introduced, hysterectomy is still associated with risk of short- and long-term complications. Given that hysterectomized women are no longer at risk of either hysterectomy or being diagnosed with endometrial or cervical cancer, it is important to describe trends in hysterectomy rates. Objective To describe trends in hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…This, in turn, could explain the negative trend over time of previous endometriosis (positive personal history may be missing among asymptomatic women in the absence of a histologic diagnosis) and long-term HRT. Overtreatment could likely have been much more frequent in the past [95,96]. This new analysis suggests that the recurrence of some clinical conditions may be due to a different attitude of gynecologists about the use of major surgery in some pathologies in the past years.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This, in turn, could explain the negative trend over time of previous endometriosis (positive personal history may be missing among asymptomatic women in the absence of a histologic diagnosis) and long-term HRT. Overtreatment could likely have been much more frequent in the past [95,96]. This new analysis suggests that the recurrence of some clinical conditions may be due to a different attitude of gynecologists about the use of major surgery in some pathologies in the past years.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, our correlation analysis showed that these recurrent clinical conditions (history of endometriosis, major surgery, HRT use) decreased significantly over time (especially after 2010). Major surgery in asymptomatic affected women or benign conditions is likely to have decreased over the years based on new and updated recommendations [1,2,95,96]. This, in turn, could explain the negative trend over time of previous endometriosis (positive personal history may be missing among asymptomatic women in the absence of a histologic diagnosis) and long-term HRT.…”
Section: Discussionmentioning
confidence: 99%
“…The foremost limitation of our analysis is the inability to establish temporality of disability preceding hysterectomy and lack of data on hysterectomy timing, indication (which generally vary by age), 44 and concomitant oophorectomy; our detection of an association cannot be interpreted as evidence of causation. We used employment as a proxy for prescription drug coverage because outpatient pharmaceutical prescriptions are excluded from universal health care in Canada and instead often covered in employer-sponsored health benefits.…”
Section: Discussionmentioning
confidence: 98%
“…16,[41][42][43] These changes in sex steroids may potentially impact on mood and may contribute to higher rates of depression following postmenopausal oophorectomy; however, it is not possible to differentiate the effects of reduced estrogens and reduced androgens in these circumstances. Other factors affecting the associations between bilateral oophorectomy at older ages and depression could include that the indication for surgery is more likely to be for cancer, 44 or that with increasing age there is a higher likelihood of comorbidities and increased physical function limitations that may be differentially higher in women with oophorectomy 45,46 that may in turn impact depression risk. Finally, rates of depression may be higher in women in midlife who experience major sociopsychological changes relating to changes in social and working status, family rearrangements or exposure to stressful events.…”
Section: Discussionmentioning
confidence: 99%